2022
DOI: 10.1039/d2qo00514j
|View full text |Cite
|
Sign up to set email alerts
|

Tandem C–N coupling/Boulton–Katritzky rearrangement reactions of 3-aminoisoxazoles or 1,2,4-oxadiazol-3-amines with 2-pyridyl trifluoromethanesulfonate: a rapid access to [1,2,4]triazolo[1,5-a]pyridines

Abstract: An efficient and convenient synthesis of functionalized [1,2,4]triazolo[1,5-a]pyridines derivates is presented. The protocol is through a palladium catalyzed tandem C-N coupling/Boulton-Katritzky rearrangement process from 3-aminoisoxazoles or 1,2,4-oxadiazol-3-amines with 2-pyridyl trifluoromethanesulfonate....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Experimentally, Pd 2 (dba) 3 /dppe was employed as a catalyst precursor, which can result in various potential resting states (see Table S1a in the Supporting Information). Calculations demonstrated that, among the considered candidates, the heterodimetallic (dppe)­Pd-Cu­(OAc) 2 species Md was most stable thermodynamically and thus set as the reference point in the whole mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, Pd 2 (dba) 3 /dppe was employed as a catalyst precursor, which can result in various potential resting states (see Table S1a in the Supporting Information). Calculations demonstrated that, among the considered candidates, the heterodimetallic (dppe)­Pd-Cu­(OAc) 2 species Md was most stable thermodynamically and thus set as the reference point in the whole mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Usually a 1,2,4-triazolo[1,5-a]pyridine system is constructed via the stepwise formation of each of the heterocycles followed by functionalization. [16,17] In contrast, our proposed approach is a one-step tandem ring-opening/double ring-closing synthesis. Our method has the following advantages: At the same time, the 1,2,4-triazolo[1,5-a]pyridine fragment is often found in the structure of biologically active substances, including tubulin polymerization inhibitors and agents for therapy of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, Zhou et al described an appropriate synthesis of functionalized triazolopyridines. [144] The reaction of 1,2,4-oxadiazoles or aminoisoxazoles with 2-pyridyl trifluoromethanesulfonates was induced by Pd(dba) 2 , L15 (Xantphos), and tBuOLi as base. The desired bicyclic compounds were isolated in medium to high yields (Scheme 121).…”
Section: Tricyclic Moleculesmentioning
confidence: 99%